PUBLIC SPEAKING INTENSIVE COURSE FOR STUDENTS OF NON-ENGLISH DEPARTMENT (A Study in English Language Centre) - Restu Mufanti; Andi Susilo; Rohfin Andria Gestanti; Elok Putri Nimasari (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2018)
Many strategies have always been used to improve students’ speaking ability, especially how to speak in front of public. To speak in public, people need to have good abilities both in verbal and non-verbal. An intensive course program of public speaking held by English Language Centre (ELC) of Universitas Muhammadiyah Ponorogo (UMPo) has been used as the program preference to enhance students’ competence in public speaking for last two years. This study aims to investigate the program of that teaching; public speaking intensive course helps students raise their speaking competency and reduce their anxiety. At the beginning of the semester, pre-test of public speaking is given to the students to know their ability before joining the program. At the end of the semester, the students are given post test and questionnaire. The questionnaire is also given to 6 instructors who involving in teaching public speaking program. The result of the students’ scores after following this program indicates that this program is successful to enhance their public speaking. The questionnaire given to the students also reveals that they can build their confidence or reduce their anxiety in speaking. This evidence is also supported by the results of questionnaire given to the instructors for asking their perception after completing this program. The result of perception entails that this program is appropriate for all students, particularly those who have passion in public speaking and want to get more benefits from it.